Enteric Phageome Alterations in Patients With Type 2 Diabetes - Chen, Qian; Ma, Xiaojing; Li, Chong; Shen, Yun; Zhu, Wei; Zhang, Yan; Guo, Xiaokui; Zhou, Jian; Liu, Chang (Frontiers in Cellular and Infection Microbiology, 2021)
Type 2 diabetes is a complex metabolic disease and has been shown to involve alteration of the gut microbiota. Previous studies have primarily focused on changes in the bacterial microbiome, while ignoring the phage community composition. Extracellular phages can lyse host bacteria and thus influence the microbiota through positive or negative interactions with bacteria. We investigated changes in the extracellular phageome and discussed its role in T2D pathogenesis. We used a sequencing-based approach to identify bacteriophage after isolation of VLPs (virus like particles) from fecal samples. We identified 330 species of phages according to the predicted host bacteria from T2D patients (N=17) and nondiabetic controls (N=29). The phageome characteristics were highly diverse among individuals. In the T2D group, the intestinal phage population was altered, and the abundance of phages specific to Enterobacteriaceae hosts increased markedly. Meanwhile, the abundance of Enterobacteriaceae bacteria in the gut was significantly increased, and systemic LPS content elevation was observed in the T2D group. Additionally, a consortia of 8 phages was found to distinguish T2D patients from nondiabetic controls with good performance (AUC>0.99).